3D-printed eye lens dosemeter holder for use in interventional radiology and interventional cardiology. (July 2020) - Surić Mihić, Marija; Pavelić, Luka; Vojnić Kortmiš, Maja; Šiško, Jerko; Maltar-Strmečki, Nadica; Prlić, Ivica
Abstract: Mandatory eye lens monitoring for exposed workers who are liable to receive an equivalent dose to the lens of the eye higher than 15 mSv in one year, required by the new European Basic Safety Standard 2013/59 and the recommendation given by the International Commission on Radiological Protection to lower the annual dose limit for the lens of the eye to 20 mSv, have put dosimetry services using Panasonic dosemeters in a difficult position. There are no commercially available eye lens dosemeter holders to fit Panasonic TLD pellets. Therefore, we designed and 3D printed inexpensive, splash proof, reusable and comfortable holders to fit a Panasonic n Li2 n B4 O7 :Cu pellet. The eye lens dosemeter consists of an acrylonitrile butadiene styrene (ABS) plastic holder with a slot for a TLD pellet. The slot with the TLD pellet is covered by a heat-shrink tube and shortly heated with hot air to shrink wrap. Results of combined energy/angular response measurements, for all photon radiation qualities used, relative to N-100 at 0° as the reference energy, were within IEC 62387:2012 limits. Additionally, electron spin resonance spectroscopy was used to test the effect of irradiation to the degradation properties of the plastic ABS holder. The dosemeter is to be worn fixed to a headband, close to the eye, on the left side of the head or in the middle of the forehead. Highlights: An inexpensive and comfortable eye lens dosimeter holder can be 3D printed. The 3D-printed holder fits a Panasonic TL single dosimeter element. Holders with Li2 B4 O7 TLD are suitable for Hp(3) measurements in IR and IC. Properties of the ABS plastic are not affected by radiation in low range.